2008
DOI: 10.1109/tns.2008.2006836
|View full text |Cite
|
Sign up to set email alerts
|

Waveform Observation of Digital Single-Event Transients Employing Monitoring >Transistor Technique

Abstract: Waveforms of digital single-event transients, radiation-induced voltage transients in logic gates, can be observed by connecting two transistors to a target logic gate. Additional transistors monitor voltage transients through their drain currents, which can be measured using the conventional 50-transmission-line technique widely used for measuring transient currents in single elementary transistors. Experimental results obtained in pulsedlaser irradiation tests demonstrate the validity of the observation tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…By using this table-based estimation method, we can obtain realistic waveforms of the DSET pulses without the need of any external 2 of 9 circuit such as variable temporal latches, self-triggering latches/flip-flops, and high drive-capability output-buffers. The estimation method has been verified by a comparison between the DSET pulse waveform estimated by using a simulated transient current waveform and the pulse-laser-induced DSET pulse waveform in an inverter cell measured by monitoring transistors [14]. In other words, we can obtain realistic waveforms of the DSET pulses without the need of any irradiation experiments.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…By using this table-based estimation method, we can obtain realistic waveforms of the DSET pulses without the need of any external 2 of 9 circuit such as variable temporal latches, self-triggering latches/flip-flops, and high drive-capability output-buffers. The estimation method has been verified by a comparison between the DSET pulse waveform estimated by using a simulated transient current waveform and the pulse-laser-induced DSET pulse waveform in an inverter cell measured by monitoring transistors [14]. In other words, we can obtain realistic waveforms of the DSET pulses without the need of any irradiation experiments.…”
Section: Introductionmentioning
confidence: 88%
“…The DSET pulse waveform at VO was determined from the table-based estimation method by using the measured current waveforms in the nMOSFET and the current-voltage characteristic of the pMOSFET. Figure 4 shows an equivalent circuit model of an inverter for the table-based estimation method (see [11][12][13][14] for further details of the table-based approach). The nMOSFET and the pMOSFET are modeled in the same configuration as it is used in an inverter connected to a self-triggering flip-flop latch chain to compare the estimated and the measured DSET pulse-widths.…”
Section: Dset Pulse-width Estimation Methodologymentioning
confidence: 99%
“…It is well known that neutron and alpha radiation generates electron-hole pairs in the well region and at the drain/source of transistors, and they supply a current large enough to cause upsets of internal retention data, i.e., soft errors. 2,3 The current may switch the magnetization of MTJs even in spintronic integrated circuits. Tsiligiannis et al have previously reported that no soft errors were observed in the static mode of commercial toggle MRAMs 4 whose writing scheme is complicated with two time-shifted large currents.…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial SETs are becoming a major reliability issue for advanced semiconductor process as the clock frequency increases [1]- [4]. Because the soft error rate of a VLSI logic chip increases with SET pulse width, many researchers have measured and simulated the SET response of logic cells or combinational circuits [5]- [8] and packaged single MOSFETs [9]- [15] built in partially and fully depleted silicon-on-insulator (PDSOI and FDSOI) devices. Pulsed laser testing is a particularly simple and rapid way to evaluate the vulnerability of ICs to soft errors.…”
Section: Introductionmentioning
confidence: 99%